Recent Advances in Graphitic Carbon Nitrides (g‐C3N4) as Photoluminescence Sensing Probe: A Review. Issue 36 (23rd September 2022) - Roy, Richa; Chacko, Anu Rose; Abraham, Thomas; Korah, Binila K; John, Bony K; Punnoose, Mamatha Susan; Mohan, Chitra; Mathew, Beena
Abstract: Among the wide range of chemosensors, the development of fluorescent chemosensors has shown continued interest in the domains of chemistry, materials, biology, and ecology due to their simple operation, low cost, high sensitivity, specificity, live observation, and short response time. As a metal‐free and fluorescent chemosensor, graphitic carbon nitride (g‐C3 N4 ) has emerged as a new research hotspot and received widespread interdisciplinary attention which is attributable to its favorable electrical band structure, high physicochemical stability, and "earth‐abundant" nature. This review summarizes the structure, synthetic methods, and various techniques for the modification of g‐C3 N4. This review also covers the development of g‐C3 N4 nanomaterials‐based sensors and their potential applications in a variety of fields. Furthermore, the comparative performance of various sensors, existing obstacles, and perspectives of g‐C3 N4 ‐based nanomaterials are also outlined in detail. Abstract : Graphitic carbon nitride as an emerging photoluminescent material: powders, quantum dots, thin films and their applications in imaging, and sensing The crystal and electronic structure of g‐C3 N4 and their synthetic approaches determine their final chemical and photophysical properties as well as the structure of materials. Potential applications in ion sensing, bio‐sensing, organics sensing, and imaging are thoroughly reviewed and discussed.